2019
DOI: 10.4236/ojog.2019.98108
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Robotic Supracervical Hysterectomy in an Ovine Animal Model: The Proof of Concept

Abstract: Objective: To gain insight into the feasibility and safety of a novel vaginal robot for performing supracervical hysterectomy in an ovine model. Introduction: The clinical application of transvaginal natural or fice transluminal endoscopic surgery (vNOTES) has broadened significantly. vNOTES reduces wound complications such as infection, hematoma formation, or herniation and is currently utilized for hysterectomy, adnexal surgery, myomectomy, and staging surgery for endometrial cancer. Robotic assistance has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…vNOTES surgeries have gained wide acceptance among gynecologists; the use of POD for peritoneal cavity inspection was described by Decker et al [14] in 1944. This concept is important as the use of the POD as a surgical port access has gained popularity for both vNOTES surgeries [15] and robotic vaginal surgery (robotic attempts at vNOTES) [9]. In vNOTES surgeries, the POD is grasped and cut into blindly using cold scissors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…vNOTES surgeries have gained wide acceptance among gynecologists; the use of POD for peritoneal cavity inspection was described by Decker et al [14] in 1944. This concept is important as the use of the POD as a surgical port access has gained popularity for both vNOTES surgeries [15] and robotic vaginal surgery (robotic attempts at vNOTES) [9]. In vNOTES surgeries, the POD is grasped and cut into blindly using cold scissors.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic attempts at vNOTES are ongoing. This concept has been previously tested in an ovine model [9]. Advantages to vNOTES technique compared with open and conventional abdominal laparoscopic/robotic surgery include avoidance of abdominal incision−related complications (wound infections, adhesions, and hernias), less postoperative pain, improved esthetics, and a diminished immunologic impact [10].…”
mentioning
confidence: 99%
“…Recently, a novel surgical system Hominis™ (Memic Innovation Surgery, Israel) that uses 2 articulated humanoid arms that can retroflex and allow 360° maneuvers have been developed and evaluated in a transvaginal supravesical hysterectomy procedure. 18 However, at the time of report, an external laparoscopic camera was utilized in the study. Although NISImagine is designed as a NOTES capable surgical robotic system, to simplify the evaluation in its feasibility to perform gynecological surgical procedures, a pure NOTES setting was not assessed at this time; however, the reversal of the robotic arms can provide a view to the surgeons as in an abdominal procedure unlike in vaginal robotic NOTES where the view is in the opposite orientation, greatly eliminating the surgeons need to adapt to a different anatomical view of the pelvic organs.…”
Section: Discussionmentioning
confidence: 99%
“…17 This study further explored the possibility of NOTES with a robotic system, adding the advantages of robotic surgery to NOTES procedures. Some studies 18,19 have suggested an ovine model is a more preferred animal model for undertaking gynecological experimental evaluation due to its similarity of the pelvic anatomy to a human female. However, for the purpose of our study, a porcine model was used as it was more representative to conduct an evaluation on the dissection field and assessment of the workspace availability in particular the maneuverability and ability of the robotic arms to reach the left and right extremities of the pelvic cavity and to form adequate triangulation.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, pigs stand out due to their pronounced anatomical and physiological resemblances to humans, rendering them a favored choice. Notably, the resemblance between the pelvic floor and genital hiatus anatomy prompted researchers to focus on sheep as a prospective model for urogenital surgery [14]. Analogous similarities extend to the urogenital realm, where organ prolapse can manifest [15].…”
Section: Animalsmentioning
confidence: 99%